Transformation of neglected corneal ulcer - Kresentia, Stevie; Surya, Amir (International Journal of Research in Medical Sciences, 2022)
A corneal ulcer is a sight-threatening condition that can be found in an outpatient clinic. Managing the corneal ulcer precisely and rapidly can minimize its symptoms and improve the vision for a better quality of life. In our case, a 52-year-old man came to the eye clinic with chief complaints of redness, tearing, blurring, and pain in his right eye three weeks ago. The other complaints were photophobia, hard to open his eye, and accompanied by yellowish secretion. He never got any medical treatment for his eye. From the examination, his visual acuity was hand movement; we found blepharospasm and lagophthalmos, conjunctiva hyperemia with chemosis, 6 mm central corneal ulcer with perilimbal neovascularization, and without hypopyon. The patient was admitted for hospitalization for intensive monitoring and treatment. The symptoms were lessened at first, but sadly there was no significant change in the vision and corneal condition. The eye condition was stable for the first week after he went home. However, the next week, the hypopyon and decemetocele show up as new manifestations and due to the patient’s delay, his condition even got worse. In consequence, patient awareness and compliance play an essential role in promoting the healing of the cornea.